(untitled) (Research, Society and Development, 2021)
Fruit by-products are the most abundant food residues, being discarded or used as feed or in composting, are major sources of bioactives with reuse potential. The objective of this work was to search for studies with agro-industrial residues from the species Persea americana and Theobroma grandflorum and to identify alternatives to reduce loss. This is an integrative review in which it was developed from the analysis of studies found in 2 databases: PubMed and Google Scholar. Studies that tested the biological activity of persea americana and theobroma grandiflorum species using plant extracts were selected. As well as how work involving food waste and possible alternatives to minimize the environmental impact was identified. Both species demonstrate significant biological actions to combat oxidative stress. Humanity requires sustainable practices of the agricultural industry for the reuse of organic waste as a strategy to reduce food waste in addition to generating biological actions of great impact.